Property Risk Assessment of Sinkhole Hazard in Louisiana, U.S.A - Mostafiz, Rubayet Bin; Friedland, Carol J.; Rohli, Robert V.; Bushra, Nazla (Frontiers in Environmental Science, 2021)
Sinkholes are an often-overlooked environmental hazard. The processes that lead to their formation are slow and insidious, which encourage a lack of awareness or concern for the potential danger, until the sudden, climactic formation leads to unexpected property damage and possibly human casualties. This research identifies the risk to residential properties to the sinkhole hazard, using Louisiana, U.S.A. as a case study. Risk is defined as the product of the hazard intensity and the loss to structure and contents within the building resulting from the hazard-related disaster. Results suggest that risk is highly scale-dependent. Although the risk due to sinkholes is small on a per capita basis statewide, especially when compared to the per capita risk of other natural hazards, the property risk for census tracts or census blocks partially or completely overlying a salt dome is substantial. At finer scales, Terrebonne Parish, in southeastern Louisiana, has the greatest concentration of salt domes, while Madison Parish, which is east of Monroe, has the highest percentage of area at risk for sinkhole formation, and St. Mary Parish – immediately west of Terrebonne – has the greatest risk of property loss. Similarly, maximum annual property losses in 2050 projected at $40,047 (2010$), in an Acadia Parish census tract, and highest projected annual per building ($43) and per capita ($18) property loss are in the same St. Mary Parish census tract. At the census block level, maximum annual property loss ($7,040) is projected in Cameron Parish, maximum annual per building loss ($85) is expected in West Baton Rouge Parish, and maximum per capita annual property loss ($120) is projected in a Plaquemines Parish census block. The method presented in this paper is developed generally, allowing application for risk assessment in other locations. The results generated by the methodology are important to local, state, and national emergency management efforts. Further, the general public of Louisiana, and other areas where the developed method is applied, may benefit by considering sinkhole risk when purchasing, remodeling, and insuring a property, including as a basis of comparison to the risk from other types of hazard.